Streptomyces-mediated growth enhancement and Bacterial Panicle Blight disease suppression in rice plants under greenhouse conditions - Ngalimat, Mohamad Syazwan; Mohd Hata, Erneeza; Zulperi, Dzarifah; Ismail, Siti Izera; Ismail, Mohd Razi; Mohd Zainudin, Nur Ain Izzati; Saidi, Noor Baity; Yusof, Mohd Termizi (Elsevier, 2022)
Streptomyces corchorusii TKR8, Streptomyces corchorusii JAS2 and Streptomyces misionensis TBS5 were previously obtained from rice fields and have been studied as a biocontrol agent against the causal agent of Bacterial Panicle Blight (BPB) disease on rice, Burkholderia glumae, and rice plant growth promoter. This study evaluated the potential of plant growth-promoting Streptomyces (PGPS) to control B. glumae and promote rice plants’ growth under greenhouse conditions. PGPS were further characterized based on their phenotypic and biochemical differences. Multilocus sequence analysis (MLSA) by amplifying gyrB, rpoB and trpB using PCR was conducted to identify the PGPS further. The antimicrobial activity of PGPS against B. glumae was investigated using a survival assay and microscopic analysis. Result indicates that JAS2 (61.2 %) utilized the highest number of carbohydrates tested, followed by TKR8 (53.1 %) and TBS5 (40.8 %) as analyzed using API 50 CH. Based on MLSA analysis of the concatenated partial sequences (1520 bp) from three housekeeping genes, the neighbor-joining tree identified JAS2 and TKR8 as S. corchorusii. Meanwhile, TBS5 as S. misionensis. Antimicrobial activity of PGPS against B. glumae has found that the supernatant of Streptomyces reduced the survival viability of B. glumae up to 50.7–70.3 %. SEM images showed that substantial morphological changes happened in cell membranes of B. glumae after the Streptomyces treatment. The highest vigor index of inoculated seedlings was determined when rice seeds were treated with a spore suspension of 1 × 107 spore/mL (for JAS2 and TKR8) and 1 × 106 spore/mL (for TBS5). Under greenhouse conditions, Streptomyces-treated plants showed improvement in rice plants' growth and grain yield and reduced the BPB disease severity. Results suggest that the S. corchorusii TKR8, S. corchorusii JAS2 and S. misionensis TBS5 should be promoted as biocontrol agents against B. glumae and bioformulations for rice crops.